Ukraine–China strategic partnership: current situation, problems and prospects - Kravchenko, Kateryna Oleksandrivna; Yu, Zheng; Dobrovolska, Nataliіa Viacheslavivna; Scryl, Iryna Anatoliivna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Purpose. The paper examines the peculiarities of the contemporary state and opportunities of further development of strategic partnership between Ukraine and China. The purpose of the paper is to study the state of implementation of the "Belt and Road Initiative" within the strategic partnership between Ukraine and China, as well as to identify threats and prospects for this form of cooperation for economic development of Ukraine.Scientific novelty. The paper analyzes the scientific achievements of domestic and foreign researchers on the possibilities of Ukraine's inclusion in the "Belt and Road Initiative", it has been analyzed the current state of strategic partnership between Ukraine and China in the aspect of the project implementation, analyzed the dynamics of bilateral trade between Ukraine and China over the past 10 years, and disclosed the commodity structure of foreign trade between the countries. Investment flows between China and Ukraine have been analyzed, implemented, projected and not implemented projects of Ukraine, which were financed by Chinese investments have been considered. SWOT analysis of straegic cooperation between Ukraine and China in terms of the "Belt and Road Initiative" was carried out and a set of recommendations for the strategic partnership development between Ukraine and China was proposed in the paper.Results. The dynamics of trade in services between Ukraine and China during the studied period had the following changes: growth was observed from 2011, 2014, 2016 and 2019, a positive balance for Ukraine was from 2009 to 2013. The structure of Ukrainian exports of services to China was dominated by: transport services 54.3%, business services 22.8%, repair and maintenance services, which do not belong to other categories 8.2%. The structure of imports of services from China was dominated by: services related to financial activities 57.7%, transport services 6.2%. Currently there is a significant imbalance in trade operations between Ukraine and the People's Republic of China. The largest share in the sectoral structure of Chinese direct investments in the share capital occupies the industry – 33.1%, in particular processing industry - 30.6%, extractive industry - 1.8%; professional and scientific-technical activities – 24.3%, as well as agriculture – 19.9% (Fig. 2). The SWOT-analysis conducted of opportunities, advantages, threats and advantages of strategic cooperation between Ukraine and China in terms of the "Belt and Road Initiative" proves the presence of a large number of possible directions for cooperation between the countries, but their successful implementation of these opportunities largely depends on the desire for cooperation between the governments of both countries.Practical significance. The results of this study can be used by the authorities at the state level to improve the conditions of strategic partnership between Ukraine and China, to attract foreign investment in the necessary sectors of the economy.